2013
DOI: 10.1039/c2cc35997a
|View full text |Cite
|
Sign up to set email alerts
|

Advances in modifying fluorescein and rhodamine fluorophores as fluorescent chemosensors

Abstract: The fluorophores based on xanthene scaffolds, mainly containing rhodamine and fluorescein dyes, have attracted considerable interest from chemists due to their excellent photophysical properties such as high absorption coefficient, high fluorescence quantum yield, high photostability and relatively long wavelengths of fluorescence emission spectra. In this feature article, we overview the strategies in the development of fluorescent probes that are operating through the modification of the skeletons of fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
140
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(143 citation statements)
references
References 86 publications
(70 reference statements)
0
140
0
3
Order By: Relevance
“…26,27 Rhodamine has excellent phototophysic properties such as high levels of absorption coefficient and quantum yield. 28 The specific amount of dye was selected by empirical method 25 and 0.3 mg/mL was chosen as the appropriate concentration for endodontic AH Plus sealer studies, as reported by our pilot study. Rhodamine B isothiocyanate did not interfere in the chemistry of the endodontic sealer.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Rhodamine has excellent phototophysic properties such as high levels of absorption coefficient and quantum yield. 28 The specific amount of dye was selected by empirical method 25 and 0.3 mg/mL was chosen as the appropriate concentration for endodontic AH Plus sealer studies, as reported by our pilot study. Rhodamine B isothiocyanate did not interfere in the chemistry of the endodontic sealer.…”
Section: Discussionmentioning
confidence: 99%
“…This colour change allows the naked-eye detection of Al 3+ or Cr 3+ or Fe 3+ ions. The new absorption band generated upon the addition of the trivalent metal ions is in the characteristic wavelength range of rhodamine and hence it is attributed that addition of Al 3+ or Cr 3+ or Fe 3+ ions to 1 induced spirolactam ring opening rhodamine moiety of 1 [14][15][16][17][18][19][20][21][22][23][24]. The absorption intensity of 1 (25 μM) at ~559 nm was enhanced by 177-fold ( = 32022 M -1 cm -1 ) with the addition of one equivalent of Al 3+ ions and the enhancement was 159-fold ( = 28579 M -1 cm -1 ) and 120-fold ( = 21530 M -1 cm -1 ), respectively for Cr 3+ and Fe 3+ ions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Digital fluorescence spectroscopy is one of the most useful method for the detection of metal ions in biological systems and hence much interest has being paid by the researchers to develop fluorescent probes for metal ion detection [14][15][16][17][18][19][20][21][22][23]. Even though several fluorescent probes are available for the detection of divalent or trivalent ions, probes useful for the collective detection of trivalent metal ions are very few in number.…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of fluorescent probes have been reported in recent years, but majority of them are useful to detect divalent metal ions (Zheng et al, 2013;Chen et al, 2012). Recently, much effort has been devoted to develop fluorescent probes for the detection trivalent metal ions like Fe 3+ or Al 3+ or Cr 3+ (Maity et al, 2012;Kim et al, 2010;Han et al, 2012;Yang et al, 2013;Sahoo et al, 2012;Nandre et al, 2014).…”
Section: Introductionmentioning
confidence: 98%